Autochthonous Probiotics Alleviate the Adverse Effects of Dietary Histamine in Juvenile Grouper (Epinephelus coioides) - Liu, Zi-Yan; Yang, Hong-Ling; Hu, Ling-Hao; Yang, Wei; Ai, Chun-Xiang; Sun, Yun-Zhang (Frontiers in Microbiology, 2021)
High dose (0.3%) of dietary histamine can cause adverse effects on growth performance, innate immunity and gut health in juvenile grouper (Epinephelus coioides). In the present study, three autochthonous probiotics (Bacillus pumilus SE5, Psychrobacter sp. SE6, and Bacillus clausii DE5) were supplemented separately to diets containing 0.3% of histamine and their effects on growth performance, innate immunity and gut health of grouper (E. coioides) were evaluated in a 56-day feeding trial. The results showed considerable increase in weight gain, specific growth rate, hepatosomatic index and decreased feed conversion rate in groupers fed with probiotic-supplemented diets. Supplementation of autochthonous probiotics has improved antioxidant capacity and innate immunity of E. coioides by measuring correlative parameters, such as total antioxidant capacity, superoxide dismutase activity, malondialdehyde content and so on. Additionally, dietary probiotics has significantly reduced the levels of serum interleukin-1β (at days 28 and 56), fatty acid-binding protein 2 and intestinal trefoil factor (at day 28), and promoted intestinal integrity following remarkably increased muscle thickness and mucosal fold height at day 56, especially in grouper fed with B. pumilus SE5 containing diet (P < 0.05). On day 56, the gut microbial composition of E. coioides were positively shaped by autochthonous probiotics, the relative abundance of potentially pathogenic Photobacterium decreased while beneficial Lactobacillus increased in fish fed with probiotic strains, especially with B. pumilus SE5 and B. clausii DE5. These results suggests that among the three autochthonous probiotic strains tested, B. pumilus SE5 is showing better efficiency in alleviating the adverse effects of (high levels) dietary histamine by decreasing the expression of inflammatory markers and also by improving the growth, innate immunity and gut health of juvenile grouper E. coioides.